Oxidative stress in oral diseases. (19th January 2015) - Kesarwala, AH; Krishna, MC; Mitchell, JB
Abstract : Oxidative species, including reactive oxygen species (ROS), are components of normal cellular metabolism and are required for intracellular processes as varied as proliferation, signal transduction, and apoptosis. In the situation of chronic oxidative stress, however, ROS contribute to various pathophysiologies and are involved in multiple stages of carcinogenesis. In head and neck cancers specifically, many common risk factors contribute to carcinogenesis via ROS‐based mechanisms, including tobacco, areca quid, alcohol, and viruses. Given their widespread influence on the process of carcinogenesis, ROS and their related pathways are attractive targets for intervention. The effects of radiation therapy, a central component of treatment for nearly all head and neck cancers, can also be altered via interfering with oxidative pathways. These pathways are also relevant to the development of many benign oral diseases. In this review, we outline how ROS contribute to pathophysiology with a focus toward head and neck cancers and benign oral diseases, describing potential targets and pathways for intervention that exploit the role of oxidative species in these pathologic processes.